The Girl Chewing Gum: The time that cinema forgot. Issue 2 (18th February 2012) - Stoneman, Rod
John Smith's Girl Chewing Gum was made in Hackney, East London and shown at the London Film-Makers' Co-op in 1976. Through its wit and imagination this film extended the forms of British avant-garde experimentation that were pervasive at that moment and mobilized a critique of narrative cinema.